The T-Shaped Engineer - Tranquillo, Joe (Journal of Engineering Education Transformations, 2017)
Much buzz has been generated around the concept of T-shaped engineers; those with both technical depth and multi-disciplinary breadth. Unfortunately, most engineering curricula compartmentalizing the depth and depth without connecting the two. This paper highlights a variety of pedagogical techniques for helping students develop a fully formed T. A range of examples are given, from entire courses and semester-long projects to short classroom exercises. A history of the T-shape is provided, ideological and practical barriers to adopting the T-shape are discussed, and opportunities for both faculty and students are highlighted.